(Re)construction of National Identity in the Lithuanian and Latvian Literary Press during the National Revival Period in the Late 20th Century - Jonkutė, Viktorija (Respectus Philologicus, 2016)
The present article, exploring the texts from Lithuanian literary weekly ‘Literatūra ir menas’, monthly ‘Pergalė/Metai’ and Latvian ‘Literatūra un Māksla’ and ‘Karogs’ of the years 1988–1992, discusses and compares the most representative episodes of (self)reflection, the changes and continuity of national identity during the time. It is shown, how collective memory, (re)created by rituals of communicative memory, participates in the (re)construction of national identity as well as tendencies of heroisation and mythologisation, cases of deconstruction, demythologisation (Suodumas, Gavelis). It is claimed that canonical impersonate expression forms of nationality and national heroes (Lačplėsis, Rainis), i.e. general cultural universals, expressions of national ideals dominate in Latvian reflections. The pantheon of individual national heroes is more fragmented and scattered in Lithuanian reflections and participates in communicative memory more passively than in Latvian. But here self-reflection and representation of exiles as collective national heroes is much more intensive